Atmospheric fate of ketolimonene part 2: Highly oxygenated molecules (HOMs) and secondary organic aerosol (SOA) formation from NO3-initiated oxidation - Sandy Solaiman; Prasanna Kumar Bej; Cécile Coeur; Nicolas Houzel; Hayley Furnell; Emma Galloway; Fabrice Cazier; Amir Ben Brik; Mixtli Campos-Pineda; Estelle Roth; Albert A. Ruth; John C. Wenger; et al. (Journal of Environmental Sciences, 2026)

A Systematic Review and Meta-Analysis of the Use of the National Institutes of Health Toolbox Cognition Battery in Clinical Populations - Kelly H. Watson; Abagail E. Ciriegio; Claire F. Miller; Marissa C. Roth; Bruce E. Compas (Neuropsychology Review, 2026)
The National Institutes of Health Toolbox Cognition Battery (NIHTB-CB) is an assessment tool that has been widely utilized in research with clinical populations across the lifespan. Despite its widespread use, a systematic review and meta-analysis of cognitive function utilizing this battery in clinical samples has not been reported. To address this gap, 84 studies were identified after systematically searching PsycINFO, PubMed, and ProQuest (71 peer-reviewed articles, 11 dissertations, 2 master’s theses) comprising 6331 clinical participants. Study quality was assessed using the QUADAS-2 tool. Results identified significant deficits in the Fluid Cognition Composite and the associated subtests (attention, working memory, processing speed, executive function) in clinical samples when compared to both the NIHTB-CB normative data and recruited comparison samples. Unexpectedly, there was some evidence that clinical participants scored higher on Crystallized Cognition subtests than the normative data but scored significantly lower than recruited controls. There was mixed evidence for performance differences on a Total Cognition Composite measure of cognitive function. There was some evidence of publication bias, and results were moderated by study quality and participant demographics. The implications of the findings for clinical research settings are discussed and suggested future directions are provided.

Atmospheric fate of ketolimonene part 1: temperature-dependent kinetics and gas-phase products from NO3-initiated oxidation - Sandy Solaiman; Prasanna Kumar Bej; Cécile Coeur; Nicolas Houzel; Hayley Furnell; Emma Galloway; Amir Ben Brik; Mixtli Campos-Pineda; Estelle Roth; Albert A. Ruth; John C. Wenger; Alexandre Tomas; et al. (Journal of Environmental Sciences, 2026)

Correction: The influence of high-load and combined high- and low-load resistance training on electromyographic behavior during an absolute muscular endurance task - Alex A. Olmos; Stephanie A. Sontag; Daniel J. Lawson; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Jaiden C. Smith; Allen L. Redinger; Michael A. Trevino (European Journal of Applied Physiology, 2026)

Exposure to a PFAS mixture alters cholesterol lipoprotein subfractions and induces a foam cell-like aortic macrophage expression profile in hyperlipidemic LDLr−/− mice - Katherine Roth; Zhao Yang; Manisha Agarwal; Katherine Gurdziel; Michael C. Petriello (Toxicology and Applied Pharmacology, 2026)

Welfare Indicators for Aquaculture Research: Toolboxes for Five Farmed European Fish Species - Chris Noble; Wout Abbink; René Alvestad; László Ardó; Marie‐Laure Bégout; Nina Bloecher; Erik Burgerhout; Josep Calduch‐Giner; Mauro Chivite‐Alcalde; Petr Císař; Evan Durland; Åsa M. Espmark; et al. (Reviews in Aquaculture, 2026)
Refining approaches to measuring, monitoring and appraising animal welfare in aquaculture research is key to (i) protecting and optimizing it, (ii) documenting the severity of how and when it deviates, and (iii) ensuring good scientific quality, reliable results and reproducibility, amongst other factors. However, different fish species and life stages can have varying welfare needs and assessing their welfare can be challenging. An array of welfare indicators (WIs) can be utilized when documenting fish welfare, and there is currently little consensus on which WIs are most applicable to the key fish species used in European aquaculture research. The aim of this review is to propose updated, fit for purpose and comprehensive WI toolboxes for aquaculture research involving Atlantic salmon ( Salmo salar ), rainbow trout ( Oncorhynchus mykiss ), European seabass ( Dicentrarchus labrax ), gilthead seabream ( Sparus aurata ), and the common carp ( Cyprinus carpio ). Where possible, these toolboxes will also include life‐stage considerations. It also provides information on utilizing WIs in deciding humane end‐points as well as information on how to sample different types of indicators. The review closes with information on how digitalization can affect the collection, collation and analysis of WI data in aquaculture research, including both practical and theoretical considerations. The toolboxes incorporate a range of WIs that go beyond those required for legally safeguarding fish welfare in both laboratory and operational experimental facilities in the current European 2010/63/EU Directive on the protection of animals used for scientific purposes and its amendment, the Commission Delegated Directive (EU) 2024/1262.

Cognitive Intra-individual Variability in Cognitively Healthy APOE ε4 Carriers, Mild Cognitive Impairment, and Alzheimer’s Disease: a Meta-analysis - Stephen L. Aita; Victor A. Del Bene; Donald L. Knapp; Claire E. Demming; Vasilios C. Ikonomou; Tyler Owen; Ivan A. Campbell; Bailey N. Wagaman; Nicholas C. Borgogna; Joshua E. Caron; Robert M. Roth; Benjamin D. Hill (Neuropsychology Review, 2025)

The influence of high-load and combined high- and low-load resistance training on electromyographic behavior during an absolute muscular endurance task - Alex A. Olmos; Stephanie A. Sontag; Daniel J. Lawson; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Jaiden C. Smith; Allen L. Redinger; Michael A. Trevino (European Journal of Applied Physiology, 2025)

Recovery of ecosystem carbon pools 35 years after whole-tree and stem-only clearcutting a red spruce – balsam fir forest in north-central Maine, USA - Inge Stupak; Bruna Barusco; Russell D. Briggs; Ivan J. Fernandez; Shawn Fraver; Agnė Grigaitė; Christopher Preece; Brian E. Roth; C. Tattersall Smith (Forest Ecology and Management, 2025)

Time-dependent fluxes and emission factors of volatile organic compounds from pig manure and solid/liquid digestates - E. Roth; C. Tape; P. Michonneau; A. Chakir (Science of The Total Environment, 2025)

Oil and gas produced water for cattle, crops, and surface water discharge: Evaluation of chemistry, toxicity and economics - Marin E. Wiltse; Brooke Ballenger; Connor B. Stewart; Tamzin A. Blewett; Claire Wadler; Holly K. Roth; Maelle Coupannec; Huma Tariq Malik; Pei Xu; Yeinner Tarazona; Yanyan Zhang; Ralf Sudowe; et al. (Journal of Hazardous Materials, 2025)

Cue relevance during navigation is a function of scale and experience - Aaron R. Krochmal; Timothy C. Roth; Nathaniel T. Simmons (Animal Behaviour, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Holocene rock varnish microstratigraphy in the Dead Sea basin and Negev Desert: Chronometric application and climatic implication - Tanzhuo Liu; Wallace S. Broecker; Sidney R. Hemming; Helena Roth; Zachary C. Dunseth; Guy D. Stiebel; Mordechai Stein (Quaternary Science Reviews, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Testing food web theory in a large lake: The role of body size in habitat coupling in Lake Michigan - Bryan M. Maitland; Harvey A. Bootsma; Charles R. Bronte; David B. Bunnell; Zachary S. Feiner; Kari H. Fenske; William W. Fetzer; Carolyn J. Foley; Brandon S. Gerig; Austin Happel; Tomas O. Höök; Friedrich W. Keppeler; et al. (Ecology, 2024)
The landscape theory of food web architecture (LTFWA) describes relationships among body size, trophic position, mobility, and energy channels that serve to couple heterogenous habitats, which in turn promotes long‐term system stability. However, empirical tests of the LTFWA are rare and support differs among terrestrial, freshwater, and marine systems. Further, it is unclear whether the theory applies in highly altered ecosystems dominated by introduced species such as the Laurentian Great Lakes. Here, we provide an empirical test of the LTFWA by relating body size, trophic position, and the coupling of different energy channels using stable isotope data from species throughout the Lake Michigan food web. We found that body size was positively related to trophic position, but for a given trophic position, organisms predominately supported by pelagic energy had smaller body sizes than organisms predominately supported by nearshore benthic energy. We also found a hump‐shaped trophic relationship in the food web where there is a gradual increase in the coupling of pelagic and nearshore energy channels with larger body sizes as well as higher trophic positions. This highlights the important role of body size and connectivity among habitats in structuring food webs. However, important deviations from expectations are suggestive of how species introductions and other anthropogenic impacts can affect food web structure in large lakes. First, native top predators appear to be flexible couplers that may provide food web resilience, whereas introduced top predators may confer less stability when they specialize on a single energy pathway. Second, some smaller bodied prey fish and invertebrates, in addition to mobile predators, coupled energy from pelagic and nearshore energy channels, which suggests that some prey species may also be important integrators of energy pathways in the system. We conclude that patterns predicted by the LTFWA are present in the face of species introductions and other anthropogenic stressors to a degree, but time‐series evaluations are needed to fully understand the mechanisms that promote stability.

Modeling of micron-sized aluminum particle combustion in hot gas flow - S. Feng; Y. Qiu; S. Xu; Z. Wu; C. Ruan; A. Roth; E. Nilsson; E. Berrocal; Z.S. Li; M. Alden; X.S. Bai (Fuel, 2024)

Loss of flavin-containing monooxygenase 3 modulates dioxin-like polychlorinated biphenyl 126-induced oxidative stress and hepatotoxicity - Manisha Agarwal; Katherine Roth; Zhao Yang; Rahul Sharma; Krishnarao Maddipati; Judy Westrick; Michael C. Petriello (Environmental Research, 2024)

Suboptimal environmental conditions prolong phage epidemics in bacterial populations - Henry Goehlich; Olivia Roth; Michael Sieber; Cynthia M. Chibani; Anja Poehlein; Jelena Rajkov; Heiko Liesegang; Carolin C. Wendling (Molecular Ecology, 2024)
Infections by filamentous phages, which are usually nonlethal to the bacterial cells, influence bacterial fitness in various ways. While phage‐encoded accessory genes, for example virulence genes, can be highly beneficial, the production of viral particles is energetically costly and often reduces bacterial growth. Consequently, if costs outweigh benefits, bacteria evolve resistance, which can shorten phage epidemics. Abiotic conditions are known to influence the net‐fitness effect for infected bacteria. Their impact on the dynamics and trajectories of host resistance evolution, however, remains yet unknown. To address this, we experimentally evolved the bacterium Vibrio alginolyticus in the presence of a filamentous phage at three different salinity levels, that is (1) ambient, (2) 50% reduction and (3) fluctuations between reduced and ambient. In all three salinities, bacteria rapidly acquired resistance through super infection exclusion (SIE), whereby phage‐infected cells acquired immunity at the cost of reduced growth. Over time, SIE was gradually replaced by evolutionary fitter surface receptor mutants (SRM). This replacement was significantly faster at ambient and fluctuating conditions compared with the low saline environment. Our experimentally parameterized mathematical model explains that suboptimal environmental conditions, in which bacterial growth is slower, slow down phage resistance evolution ultimately prolonging phage epidemics. Our results may explain the high prevalence of filamentous phages in natural environments where bacteria are frequently exposed to suboptimal conditions and constantly shifting selections regimes. Thus, our future ocean may favour the emergence of phage‐born pathogenic bacteria and impose a greater risk for disease outbreaks, impacting not only marine animals but also humans.

Distinct fungal and bacterial responses to fire severity and soil depth across a ten-year wildfire chronosequence in beetle-killed lodgepole pine forests - Marcos V. Caiafa; Amelia R. Nelson; Thomas Borch; Holly K. Roth; Timothy S. Fegel; Charles C. Rhoades; Michael J. Wilkins; Sydney I. Glassman (Forest Ecology and Management, 2023)

Ganymede's atmosphere as constrained by HST/STIS observations - F. Leblanc; L. Roth; J.Y. Chaufray; R. Modolo; M. Galand; N. Ivchenko; G. Carnielli; C. Baskevitch; A. Oza; A.L.E. Werner (Icarus, 2023)

Wild Australian magpies learn to pull intact, not broken, strings to obtain food - Robin D. Johnsson; Papillon S. Veillet; Farley Connelly; John A. Endler; Timothy C. Roth; John A. Lesku (Behavioral Ecology and Sociobiology, 2023)
The string-pulling paradigm is an approach commonly used in the study of animal cognition to investigate problem-solving abilities. This test involves an out-of-reach reward that can only be acquired through pulling a string. Australian magpies ( Gymnorhina tibicen tyrannica ) can solve cognitive tasks requiring associative and reversal learning, spatial memory, and inhibitory control. Nonetheless, whether magpies can pass a test of means-end understanding—the string-pull test—is unclear. We tested wild magpies on a string-pulling task with five configurations, including a long loose string that required several pulls to obtain food, a short string that only required a single pull to complete, and two short strings—one intact and connected to the food reward; the other broken and unable to yield food when pulled. Of the 11 magpies tested, none solved the long string task at first presentation. Two naïve birds and three, subsequently trained, birds succeeded at the short string. Once proficient at the short string, four of these five birds then solved the long string task; in addition, three learned to choose a functional, intact string over a non-functional, broken string. Overall, these observations provide evidence that Australian magpies have the ability to solve string-pulling tasks but it remains unclear whether they do so by trial-and-error or if they possess means-end understanding. Significance statement We found, for the first time, that wild, free-ranging Australian magpies can learn to solve different versions of a string-pulling task; a version with a short string, a long string, and two strings next to each other where one of them was broken and non-functional (broken string task). Some magpies spontaneously solved the task with the short string, where other magpies required training, and magpies only managed to solve the task with the long string after they had succeeded on the short string task. Furthermore, some of the magpies solved the broken string task but required a high number of trials to do so. Overall, our findings show that Australian magpies have the ability to solve string-pulling tasks but it remains unclear whether they do so by trial-and-error or if they understand causal relations between objects.

The case for investigating the cognitive map in nonavian reptiles - Aaron R. Krochmal; Timothy C. Roth (Animal Behaviour, 2023)

The 2022 Diadema antillarum die-off event: Comparisons with the 1983-1984 mass mortality - Alwin Hylkema; Kimani Kitson-Walters; Patricia R. Kramer; Joshua T. Patterson; Lynnette Roth; Moriah L. B. Sevier; Maria Vega-Rodriguez; Matthew M. Warham; Stacey M. Williams; Judith C. Lang (Frontiers in Marine Science, 2023)
The 1983-1984 die-off of the long-spined sea urchin Diadema antillarum stands out as a catastrophic marine event because of its detrimental effects on Caribbean coral reefs. Without the grazing activities of this key herbivore, turf and macroalgae became the dominant benthic group, inhibiting coral recruitment and compromising coral reef recovery from other disturbances. In the decades that followed, recovery of D. antillarum populations was slow to non-existent. In late January 2022, a new mass mortality of D. antillarum was first observed in the U.S. Virgin Islands. We documented the spread and extent of this new die-off using an online survey. Infected individuals were closely monitored in the lab to record signs of illness, while a large population on Saba, Dutch Caribbean, was surveyed weekly before and during mortality to determine the lethality of this event. Within four months the die-off was distributed over 1,300 km from north to south and 2,500 km east to west. Whereas the 1983-1984 die-off advanced mostly with the currents, the 2022 event has appeared far more quickly in geographically distant areas. First die-off observations in each jurisdiction were often close to harbor areas, which, together with their rapid appearance, suggests that anthropogenic factors may have contributed to the spread of the causative agent. The signs of illness in sick D. antillarum were very similar to those recorded during the 1983-1984 die-off: lack of tube feet control, slow spine reaction followed by their loss, and necrosis of the epidermis were observed in both lab and wild urchins. Affected populations succumbed fast; within a month of the first signs of illness, a closely monitored population at Saba, Dutch Caribbean, had decreased from 4.05 individuals per m 2 to 0.05 individuals per m 2 . Lethality can therefore be as high as 99%. The full extent of the 2022 D. antillarum die-off event is not currently known. The slower spread in the summer of 2022 might indicate that the die-off is coming to a (temporary) standstill. If this is the case, some populations will remain unaffected and potentially supply larvae to downstream areas and augment natural recovery processes. In addition, several D. antillarum rehabilitation approaches have been developed in the past decade and some are ready for large scale implementation. However, active conservation and restoration should not distract from the primary goal of identifying a cause and, if possible, implementing actions to decrease the likelihood of future D. antillarum die-off events.

Demonstration of Reversible Dispersion in a Darcy-Scale Push-Pull Laboratory Experiment - Roseanna M. Neupauer; Eric J. Roth; John P. Crimaldi; David C. Mays; Lauren J. Sather (Transport in Porous Media, 2023)

Dive characteristics of Cross Seamount beaked whales from long‐term passive acoustic monitoring at the Pacific Missile Range Facility, Kauaʻi - Roanne Manzano‐Roth; E. Elizabeth Henderson; Gabriela C. Alongi; Cameron R. Martin; Stephen W. Martin; Brian Matsuyama (Marine Mammal Science, 2023)
Beaked whale foraging pulses were detected on the Pacific Missile Range Facility (PMRF) off Kauaʻi, Hawaiʻi, via long term passive acoustic monitoring. The unidentified pulses do not match foraging pulses of known species on the range but are similar to the unidentified beaked whale first detected at Cross Seamount, Hawaiʻi. Although there has not been a visual confirmation of the unidentified beaked whale species, analysis of data collected from 2007 to 2019 has identified beaked whale foraging dive characteristics from echolocation pulses. From the 13 years of data, the most distinct patterns were that all foraging dives occurred at night and the nighttime foraging dive rate was 0.11 group vocal periods (GVP) per hour, with most detections on shallow hydrophones (625–1,000 m deep) over steep bathymetric slopes. Data collected during U.S. Navy training events were used to compare dive behavior during mid‐frequency active sonar (MFAS) activity against baseline periods; it was determined that the whales reduced GVPs during sonar and these remained low for at least 3 days after the training events. These results are the first long‐term record of acoustic signals from the Cross Seamount beaked whale and provide important insights into their habitat use and occurrence patterns.

High spatiotemporal variability of methane concentrations challenges estimates of emissions across vegetated coastal ecosystems - Florian Roth; Xiaole Sun; Marc C. Geibel; John Prytherch; Volker Brüchert; Stefano Bonaglia; Elias Broman; Francisco Nascimento; Alf Norkko; Christoph Humborg (Global Change Biology, 2022)
Coastal methane (CH 4 ) emissions dominate the global ocean CH 4 budget and can offset the “blue carbon” storage capacity of vegetated coastal ecosystems. However, current estimates lack systematic, high‐resolution, and long‐term data from these intrinsically heterogeneous environments, making coastal budgets sensitive to statistical assumptions and uncertainties. Using continuous CH 4 concentrations, δ 13 C‐CH 4 values, and CH 4 sea–air fluxes across four seasons in three globally pervasive coastal habitats, we show that the CH 4 distribution is spatially patchy over meter‐scales and highly variable in time. Areas with mixed vegetation, macroalgae, and their surrounding sediments exhibited a spatiotemporal variability of surface water CH 4 concentrations ranging two orders of magnitude (i.e., 6–460 nM CH 4 ) with habitat‐specific seasonal and diurnal patterns. We observed (1) δ 13 C‐CH 4 signatures that revealed habitat‐specific CH 4 production and consumption pathways, (2) daily peak concentration events that could change >100% within hours across all habitats, and (3) a high thermal sensitivity of the CH 4 distribution signified by apparent activation energies of ~1 eV that drove seasonal changes. Bootstrapping simulations show that scaling the CH 4 distribution from few samples involves large errors, and that ~50 concentration samples per day are needed to resolve the scale and drivers of the natural variability and improve the certainty of flux calculations by up to 70%. Finally, we identify northern temperate coastal habitats with mixed vegetation and macroalgae as understudied but seasonally relevant atmospheric CH 4 sources (i.e., releasing ≥ 100 μmol CH 4 m −2 day −1 in summer). Due to the large spatial and temporal heterogeneity of coastal environments, high‐resolution measurements will improve the reliability of CH 4 estimates and confine the habitat‐specific contribution to regional and global CH 4 budgets.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Lean mass sparing in resistance-trained athletes during caloric restriction: the role of resistance training volume - C. Roth; B. J. Schoenfeld; M. Behringer (European Journal of Applied Physiology, 2022)
Many sports employ caloric restriction (CR) to reduce athletes’ body mass. During these phases, resistance training (RT) volume is often reduced to accommodate recovery demands. Since RT volume is a well-known anabolic stimulus, this review investigates whether a higher training volume helps to spare lean mass during CR. A total of 15 studies met inclusion criteria. The extracted data allowed calculation of total tonnage lifted (repetitions × sets × intensity load) or weekly sets per muscle group for only 4 of the 15 studies, with RT volume being highly dependent on the examined muscle group as well as weekly training frequency per muscle group. Studies involving high RT volume programs (≥ 10 weekly sets per muscle group) revealed low-to-no (mostly female) lean mass loss. Additionally, studies increasing RT volume during CR over time appeared to demonstrate no-to-low lean mass loss when compared to studies reducing RT volume. Since data regarding RT variables applied were incomplete in most of the included studies, evidence is insufficient to conclude that a higher RT volume is better suited to spare lean mass during CR, although data seem to favor higher volumes in female athletes during CR. Moreover, the data appear to suggest that increasing RT volume during CR over time might be more effective in ameliorating CR-induced atrophy in both male and female resistance-trained athletes when compared to studies reducing RT volume. The effects of CR on lean mass sparing seem to be mediated by training experience, pre-diet volume, and energy deficit, with, on average, women tending to spare more lean mass than men. Potential explanatory mechanisms for enhanced lean mass sparing include a preserved endocrine milieu as well as heightened anabolic signaling.

Combined effects of heatwaves and micropollutants on freshwater ecosystems: Towards an integrated assessment of extreme events in multiple stressors research - Francesco Polazzo; Sabrina K. Roth; Markus Hermann; Annika Mangold‐Döring; Andreu Rico; Anna Sobek; Paul J. Van den Brink; Michelle C. Jackson (Global Change Biology, 2022)
Freshwater ecosystems are strongly influenced by weather extremes such as heatwaves (HWs), which are predicted to increase in frequency and magnitude in the future. In addition to these climate extremes, the freshwater realm is impacted by the exposure to various classes of chemicals emitted by anthropogenic activities. Currently, there is limited knowledge on how the combined exposure to HWs and chemicals affects the structure and functioning of freshwater ecosystems. Here, we review the available literature describing the single and combined effects of HWs and chemicals on different levels of biological organization, to obtain a holistic view of their potential interactive effects. We only found a few studies (13 out of the 61 studies included in this review) that investigated the biological effects of HWs in combination with chemical pollution. The reported interactive effects of HWs and chemicals varied largely not only within the different trophic levels but also depending on the studied endpoints for populations or individuals. Hence, owing also to the little number of studies available, no consistent interactive effects could be highlighted at any level of biological organization. Moreover, we found an imbalance towards single species and population experiments, with only five studies using a multitrophic approach. This results in a knowledge gap for relevant community and ecosystem level endpoints, which prevents the exploration of important indirect effects that can compromise food web stability. Moreover, this knowledge gap impairs the validity of chemical risk assessments and our ability to protect ecosystems. Finally, we highlight the urgency of integrating extreme events into multiple stressors studies and provide specific recommendations to guide further experimental research in this regard.

Neuroinflammation in Primary Cultures of the Rat Spinal Dorsal Horn Is Attenuated in the Presence of Adipose Tissue–Derived Medicinal Signalling Cells (AdMSCs) in a Co-cultivation Model - Stephan Leisengang; Laura B. Heilen; Michele C. Klymiuk; Franz Nürnberger; Daniela Ott; Kathrin Wolf-Hofmann; Rüdiger Gerstberger; Christoph Rummel; Martin J. Schmidt; Stefan Arnhold; Joachim Roth (Molecular Neurobiology, 2022)
Neuroinflammation within the superficial dorsal horn (SDH) of the spinal cord induces inflammatory pain with symptoms of hyperalgesia and allodynia. Glial activation and production of inflammatory mediators (e.g. cytokines) is associated with modulation of nociceptive signalling. In this context, medicinal signalling cells, e.g. obtained from adipose tissue (AdMSCs), gained attention due to their capacity to modulate the inflammatory response in several diseases, e.g. spinal cord injury. We applied the recently established mixed neuroglial primary cell culture of the rat SDH to investigate effects of AdMSCs on the inflammatory response of SDH cells. Following establishment of a co-cultivation system, we performed specific bioassays for tumour necrosis factor alpha (TNFα) and interleukin (IL)-6, RT-qPCR and immunocytochemistry to detect changes in cytokine production and glial activation upon inflammatory stimulation with lipopolysaccharide (LPS). LPS-induced expression and release of pro-inflammatory cytokines (TNFα, IL-6) by SDH cells was significantly attenuated in the presence of AdMSCs. Further evidence for anti-inflammatory capacities of AdMSCs derived from a blunted LPS-induced TNFα/IL-10 expression ratio and suppressed nuclear translocation of the inflammatory transcription factor nuclear factor kappa B (NFκB) in SDH microglial cells. Expression of IL-10, transforming growth factor beta (TGF-β) and TNFα-stimulated gene-6 (TSG-6) was detected in AdMSCs, which are putative candidates for anti-inflammatory capacities of these cells. We present a novel co-cultivation system of AdMSCs with neuroglial primary cultures of the SDH to investigate immunomodulatory effects of AdMSCs at a cellular level.

Measuring circulating triglycerides in free-living birds: evaluation of a field-usable point-of-care analyzer for American woodcock - Christopher M. Roelandt; Amber M. Roth; Scott R. McWilliams; Jill C. Witt (Journal of Ornithology, 2022)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Methods for Laser-Induced Fluorescence Imaging of Solute Plumes at the Darcy Scale in Quasi-Two-Dimensional, Refractive Index-Matched Porous Media - Eric J. Roth; David C. Mays; Roseanna M. Neupauer; Lauren J. Sather; John P. Crimaldi (Transport in Porous Media, 2021)

Simultaneous Measurements of Dinitrogen Fixation and Denitrification Associated With Coral Reef Substrates: Advantages and Limitations of a Combined Acetylene Assay - Yusuf C. El-Khaled; Florian Roth; Nils Rädecker; Najeh Kharbatia; Burton H. Jones; Christian R. Voolstra; Christian Wild (Frontiers in Marine Science, 2020)

Reassessing Potential for Exotic Larch in Northern United States - David I Maass; Lloyd C Irland; James L Anderson; Kenneth M Laustsen; Michael S Greenwood; Brian E Roth (Journal of Forestry, 2020)
Abstract Field measurements of operational plantations and research plots demonstrate that growth rates of exotic larches in unmanaged stands can exceed 12 m3 per hectare per year in Maine and elsewhere. This paper briefly reviews the recent history of exotic larch (Larix decidua, L. kaempferi, and L. × marschlinsii) in northeastern United States and Canada. Stands can be commercially thinned as early as 15 years; further thinnings add to significant volume accumulation, based on stand table projections. Genetic development of the hybrid (L. × marschlinsii) could yield additional volume. Even at current low stumpage values, exotic larch plantations offer positive returns at realistic discount rates. In map form, we report a current inventory of known trials and operational plantings across the Northern United States, including adjacent Canada.

Wall Effect Mitigation Techniques for Experiments with Planar Walls - Eric J. Roth; Roseanna M. Neupauer; David C. Mays; Lauren J. Sather; John P. Crimaldi (Transport in Porous Media, 2020)

Electroplating for chromium removal from tannery wastewater - G. S. da Silva; F. A. dos Santos; G. Roth; C. L. C. Frankenberg (International Journal of Environmental Science and Technology, 2020)

Irritable Bowel Syndrome, Immune Fitness, and Insomnia: Results from an Online Survey Among People Reporting Sleep Complaints - Smedra Abdulahad; Hendrikje Huls; Stephanie Balikji; Aurora J. A. E. van de Loo; Thomas Roth; Joris C. Verster (Sleep and Vigilance, 2019)

Airflow Simulations in Infant, Child, and Adult Pulmonary Conducting Airways - Jessica M. Oakes; Steven C. Roth; Shawn C. Shadden (Annals of Biomedical Engineering, 2018)

Climate change effects on livestock in the Northeast US and strategies for adaptation - A. N. Hristov; A. T. Degaetano; C. A. Rotz; E. Hoberg; R. H. Skinner; T. Felix; H. Li; P. H. Patterson; G. Roth; M. Hall; T. L. Ott; L. H. Baumgard; et al. (Climatic Change, 2018)

The effects of warming and ocean acidification on growth, photosynthesis, and bacterial communities for the marine invasive macroalga Caulerpa taxifolia - Alexandra J. Roth‐Schulze; Torsten Thomas; Peter Steinberg; Marty R. Deveney; Jason E. Tanner; Kathryn H. Wiltshire; Stephanie Papantoniou; John W. Runcie; C. Frederico D. Gurgel (Limnology and Oceanography, 2018)
Caulerpa taxifolia is a pantropical green benthic marine macroalga, and one of the best known marine invasive species in temperate coastal habitats. In Australia, this species has been introduced to seven estuaries along New South Wales and one in South Australia. How this alga will perform under future climate change scenarios is however not well defined. This study experimentally assessed the effects of ocean acidification and global warming on the growth, photosynthetic performance and the bacterial community on two populations of C. taxifolia , one native and one invasive. A range of complex significant interactive effects between pH, temperature, and initial plant size on the growth of C. taxifolia were observed, but no effect of population origin and photosystem II (PSII) fluorescence quantum yield parameters were detected. No significant effects of the treatment combinations were observed on bacterial community richness or diversity. Only one bacterial species out of 1087 present on the algae showed significant changes between pH treatments at high temperature (24°C). This bacterium belonged to the genus Planctomyces and its relative abundance was more than 10 times higher in samples with low pH compared to the control. Higher plant growth was observed under all higher pCO 2 and lower pH conditions suggesting that C. taxifolia will benefit from climate change, posing a potential higher risk in invaded locations.

The Impact of Having a 15-min Break With and Without Consuming an Energy Drink on Prolonged Simulated Highway Driving - Joris C. Verster; Aurora J. A. E. van de Loo; Adriana C. Bervoets; Loes Mooren; Thomas Roth (Sleep and Vigilance, 2017)

A biological blueprint for the axons of superficial layer pyramidal cells in cat primary visual cortex - Kevan A. C. Martin; Stephan Roth; Elisha S. Rusch (Brain Structure and Function, 2017)

Synaptic connections formed by patchy projections of pyramidal cells in the superficial layers of cat visual cortex - German Koestinger; Kevan A. C. Martin; Stephan Roth; Elisha S. Rusch (Brain Structure and Function, 2017)

Alcohol Hangover, Sleep Quality, and Daytime Sleepiness - Marith van Schrojenstein Lantman; Thomas Roth; Timothy Roehrs; Joris C. Verster (Sleep and Vigilance, 2017)

Mainstreaming the social sciences in conservation - Nathan J. Bennett; Robin Roth; Sarah C. Klain; Kai M. A. Chan; Douglas A. Clark; Georgina Cullman; Graham Epstein; Michael Paul Nelson; Richard Stedman; Tara L. Teel; Rebecca E. W. Thomas; Carina Wyborn; et al. (Conservation Biology, 2017)
Despite broad recognition of the value of social sciences and increasingly vocal calls for better engagement with the human element of conservation, the conservation social sciences remain misunderstood and underutilized in practice. The conservation social sciences can provide unique and important contributions to society's understanding of the relationships between humans and nature and to improving conservation practice and outcomes. There are 4 barriers—ideological, institutional, knowledge, and capacity—to meaningful integration of the social sciences into conservation. We provide practical guidance on overcoming these barriers to mainstream the social sciences in conservation science, practice, and policy. Broadly, we recommend fostering knowledge on the scope and contributions of the social sciences to conservation, including social scientists from the inception of interdisciplinary research projects, incorporating social science research and insights during all stages of conservation planning and implementation, building social science capacity at all scales in conservation organizations and agencies, and promoting engagement with the social sciences in and through global conservation policy‐influencing organizations. Conservation social scientists, too, need to be willing to engage with natural science knowledge and to communicate insights and recommendations clearly. We urge the conservation community to move beyond superficial engagement with the conservation social sciences. A more inclusive and integrative conservation science—one that includes the natural and social sciences—will enable more ecologically effective and socially just conservation. Better collaboration among social scientists, natural scientists, practitioners, and policy makers will facilitate a renewed and more robust conservation. Mainstreaming the conservation social sciences will facilitate the uptake of the full range of insights and contributions from these fields into conservation policy and practice.

Applicability of APSIM to capture the effectiveness of irrigation management decisions in rice-based cropping sequence in the Upper-Gangetic Plains of India - N. Subash; M. Shamim; V. K. Singh; B. Gangwar; B. Singh; D. S. Gaydon; C. H. Roth; P. L. Poulton; A. K. Sikka (Paddy and Water Environment, 2015)

Absence of hybridisation between Fuscospora species at a site in Arthur's Pass National Park, New Zealand - RD Smissen; C Mitchell; M Roth; PB Heenan (New Zealand Journal of Botany, 2015)
We analysed simple sequence repeat markers for a selection of red beech ( Fuscospora fusca ) and mountain beech ( Fuscospora cliffortioides ) trees growing together and for seeds collected from them. Our analysis detected neither hybrid trees nor hybrid seeds within our sample. We suggest pre‐zygotic reproductive isolating mechanisms such as differences in flowering time may be important in maintaining boundaries between Fuscospora species despite extensive sympatry.

Genome and physiology of the ascomycete filamentous fungus X eromyces bisporus , the most xerophilic organism isolated to date - Su‐lin L. Leong; Henrik Lantz; Olga V. Pettersson; Jens C. Frisvad; Ulf Thrane; Hermann J. Heipieper; Jan Dijksterhuis; Manfred Grabherr; Mats Pettersson; Christian Tellgren‐Roth; Johan Schnürer (Environmental Microbiology, 2015)
Summary X eromyces bisporus can grow on sugary substrates down to 0.61, an extremely low water activity. Its genome size is approximately 22 Mb . Gene clusters encoding for secondary metabolites were conspicuously absent; secondary metabolites were not detected experimentally. Thus, in its ‘dry’ but nutrient‐rich environment, X . bisporus appears to have relinquished abilities for combative interactions. Elements to sense/signal osmotic stress, e.g. HogA pathway, were present in X . bisporus . However, transcriptomes at optimal (∼ 0.89) versus low a w (0.68) revealed differential expression of only a few stress‐related genes; among these, certain (not all) steps for glycerol synthesis were upregulated. X eromyces bisporus increased glycerol production during hypo‐ and hyper‐osmotic stress, and much of its wet weight comprised water and rinsable solutes; leaked solutes may form a protective slime. X eromyces bisporus and other food‐borne moulds increased membrane fatty acid saturation as water activity decreased. Such modifications did not appear to be transcriptionally regulated in X . bisporus ; however, genes modulating sterols, phospholipids and the cell wall were differentially expressed. X eromyces bisporus was previously proposed to be a ‘chaophile’, preferring solutes that disorder biomolecular structures. Both X . bisporus and the closely related xerophile, X erochrysium xerophilum , with low membrane unsaturation indices, could represent a phylogenetic cluster of ‘chaophiles’.

Nanosecond pulsed electric fields modulate the expression of Fas/CD95 death receptor pathway regulators in U937 and Jurkat Cells - Larry E. Estlack; Caleb C. Roth; Gary L. Thompson; William A. Lambert; Bennett L. Ibey (Apoptosis, 2014)

Impact of raw pig slurry and pig farming practices on physicochemical parameters and on atmospheric N2O and CH4 emissions of tropical soils, Uvéa Island (South Pacific) - E. Roth; P. Gunkel-Grillon; L. Joly; X. Thomas; T. Decarpenterie; I. Mappe-Fogaing; C. Laporte-Magoni; N. Dumelié; G. Durry (Environmental Science and Pollution Research, 2014)

Effects of alcohol hangover on simulated highway driving performance - Joris C. Verster; Adriana C. Bervoets; Suzanne de Klerk; Rick A. Vreman; Berend Olivier; Thomas Roth; Karel A. Brookhuis (Psychopharmacology, 2014)

Lapses of attention as outcome measure of the on-the-road driving test - Joris C Verster; Adriana C Bervoets; Suzanne de Klerk; Thomas Roth (Psychopharmacology, 2014)

Neonatal steroids induce a down-regulation of tenascin-C and elastin and cause a deceleration of the first phase and an acceleration of the second phase of lung alveolarization - Matthias Roth-Kleiner; Thomas M. Berger; Sandrine Gremlich; Stefan A. Tschanz; Sonja I. Mund; Martin Post; Marco Stampanoni; Johannes C. Schittny (Histochemistry and Cell Biology, 2014)

Assessment of Juvenile Pigs to Serve as Human Pediatric Surrogates for Preclinical Formulation Pharmacokinetic Testing - Wyatt J. Roth; Candice B. Kissinger; Robyn R. McCain; Bruce R. Cooper; Jeremy N. Marchant-Forde; Rachel C. Vreeman; Sophia Hannou; Gregory T. Knipp (The AAPS Journal, 2013)

Differential hippocampal gene expression is associated with climate‐related natural variation in memory and the hippocampus in food‐caching chickadees - V. V. Pravosudov; T. C. Roth; M. L. Forister; L. D. LaDage; R. Kramer; F. Schilkey; A. M. van der Linden (Molecular Ecology, 2013)
There is significant and often heritable variation in cognition and its underlying neural mechanisms, yet specific genetic contributions to such variation are not well characterized. Black‐capped chickadees present a good model to investigate the genetic basis of cognition because they exhibit tremendous climate‐related variation in memory, hippocampal morphology and neurogenesis rates throughout the North American continent, and these cognitive traits appear to have a heritable basis. We examined the hippocampal transcriptome profiles of laboratory‐reared chickadees from the two most divergent populations to test whether differential gene expression in the hippocampus is associated with population differences in spatial memory, hippocampal morphology and adult hippocampal neurogenesis rates. Using high‐resolution mRNA sequencing coupled to a de novo transcriptome assembly, we generated 23 295 consensus sequences, which predicted 16 206 protein sequences with 13 982 showing high similarity to known protein sequences or conserved hypothetical proteins in other species. Of these, we identified differential expression in nearly 380 genes, with 47 genes specifically linked to neurogenesis, apoptosis, synaptic function, and learning and memory processes. Many of the other differentially expressed genes, however, may be associated with other functions. Our study presents the first avian hippocampal transcriptome, and it is the first study identifying differential gene expression associated with natural variation in cognition and the hippocampus. Our results provide additional support to the hypothesis that population differences in memory, hippocampal morphology and neurogenesis in chickadees have likely resulted from natural selection that appears to act on memory and its underlying neural mechanisms.

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Population genetic structure and its implications for adaptive variation in memory and the hippocampus on a continental scale in food‐caching black‐capped chickadees - V. V. Pravosudov; T. C. Roth; M. L. Forister; L. D. LaDage; T. M. Burg; M. J. Braun; B. S. Davidson (Molecular Ecology, 2012)
Food‐caching birds rely on stored food to survive the winter, and spatial memory has been shown to be critical in successful cache recovery. Both spatial memory and the hippocampus, an area of the brain involved in spatial memory, exhibit significant geographic variation linked to climate‐based environmental harshness and the potential reliance on food caches for survival. Such geographic variation has been suggested to have a heritable basis associated with differential selection. Here, we ask whether population genetic differentiation and potential isolation among multiple populations of food‐caching black‐capped chickadees is associated with differences in memory and hippocampal morphology by exploring population genetic structure within and among groups of populations that are divergent to different degrees in hippocampal morphology. Using mitochondrial DNA and 583 AFLP loci, we found that population divergence in hippocampal morphology is not significantly associated with neutral genetic divergence or geographic distance, but instead is significantly associated with differences in winter climate. These results are consistent with variation in a history of natural selection on memory and hippocampal morphology that creates and maintains differences in these traits regardless of population genetic structure and likely associated gene flow.

Leaf Surface Wettability and Implications for Drop Shedding and Evaporation from Forest Canopies - W. Konrad; M. Ebner; C. Traiser; A. Roth-Nebelsick (Pure and Applied Geophysics, 2012)

Selected Trace Elements in the Sacramento River, California: Occurrence and Distribution - H. E. Taylor; R. C. Antweiler; D. A. Roth; C. N. Alpers; P. Dileanis (Archives of Environmental Contamination and Toxicology, 2012)

Lack of ceruloplasmin expression alters aspects of copper transport to the fetus and newborn, as determined in mice - Yu-Ling Chu; Eric N. Sauble; Anthony Cabrera; Aleeza Roth; M. Leigh Ackland; Julian F. B. Mercer; Maria C. Linder (BioMetals, 2012)

Predicting psychopharmacological drug effects on actual driving performance (SDLP) from psychometric tests measuring driving-related skills - Joris C. Verster; Thomas Roth (Psychopharmacology, 2012)

Drivers can poorly predict their own driving impairment: a comparison between measurements of subjective and objective driving quality - Joris C. Verster; Thomas Roth (Psychopharmacology, 2012)

Does insulin-like growth factor 1 genotype influence muscle power response to strength training in older men and women? - Suchi Sood; Erik D. Hanson; Matthew J. Delmonico; Matthew C. Kostek; Brian D. Hand; Stephen M. Roth; Ben F. Hurley (European Journal of Applied Physiology, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Using the spectral scaling exponent for validation of quantitative precipitation forecasts - T.-Y. Koh; B. C. Bhatt; K. K. W. Cheung; C. K. Teo; Y. H. Lee; Matthias Roth; Purnawirman (Meteorology and Atmospheric Physics, 2012)

Protein Kinase B (Akt) and Mitogen-Activated Protein Kinase p38α in Retinal Ischemic Post-Conditioning - John C. Dreixler; Ajay Sampat; Afzhal R. Shaikh; Michael Alexander; Marcus M. Marcet; Steven Roth (Journal of Molecular Neuroscience, 2011)

A novel gammaherpesvirus isolated from a black-tailed prairie dog (Cynomys ludovicianus) - Brandy Nagamine; Leandro Jones; Christian Tellgren-Roth; Jacqueline Cavender; Ana C. Bratanich (Archives of Virology, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

The armadillo repeat domain of Apc suppresses intestinal tumorigenesis - Richard C. Crist; Jacquelyn J. Roth; Amy A. Baran; Benjamin J. McEntee; Linda D. Siracusa; Arthur M. Buchberg (Mammalian Genome, 2010)

A simulation of food‐web interactions leading to rainbow smelt Osmerus mordax dominance in Sparkling Lake, Wisconsin - B. M. Roth; T. R. Hrabik; C. T. Solomon; N. Mercado‐Silva; J. F. Kitchell (Journal of Fish Biology, 2010)
A process‐based simulation model was used to examine the nature and intensity of food‐web interactions that allow Osmerus mordax to dominate invaded lakes. The model simulates food‐web interactions among linked populations of O. mordax , Coregonus artedi and Sander vitreus . Simulations indicated that O. mordax dominate where: (1) adult O. mordax prey on young‐of‐the‐year (YOY) C. artedi , (2) YOY O. mordax negatively affect YOY S. vitreus through competition and (3) adult S. vitreus experience moderate fishing mortality. Osmerus mordax dominated simulations across a broad range of variable values that regulated competition and predation, and displayed threshold responses to increasing angler harvest. Consequently, angler harvest should be carefully managed in lakes susceptible to O. mordax invasions because the alternative could lead to fishery collapse.

Adaptive clustering of airborne LiDAR data to segment individual tree crowns in managed pine forests - H. Lee; K. C. Slatton; B. E. Roth; W. P. Cropper (International Journal of Remote Sensing, 2010)

Contribution of Oil Industry Activities to Environmental Loads of Heavy Metals in the Tabasco Lowlands, Mexico - S. Fiedler; C. Siebe; A. Herre; B. Roth; S. Cram; K. Stahr (Water, Air, & Soil Pollution, 2009)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Prediction of forest canopy light interception using three‐dimensional airborne LiDAR data - H. Lee; K. C. Slatton; B. E. Roth; W. P. Cropper (International Journal of Remote Sensing, 2009)

BLOC1S2 interacts with the HIPPI protein and sensitizes NCH89 glioblastoma cells to apoptosis - Georg Gdynia; Judith Lehmann-Koch; Sebastian Sieber; Katrin E. Tagscherer; Anne Fassl; Hanswalter Zentgraf; Shu-Ichi Matsuzawa; John C. Reed; Wilfried Roth (Apoptosis, 2008)

Urban Climatology ICUC6 - C. S. B. Grimmond; W. Kuttler; S. Lindqvist; M. Roth (International Journal of Climatology, 2007)

Recombinant full-length human IgG1s targeting hormone-refractory prostate cancer - Bin Liu; Fraser Conrad; Audrey Roth; Daryl C. Drummond; Jeff P. Simko; James D. Marks (Journal of Molecular Medicine, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Preserved dynamic cerebral autoregulation in the middle cerebral artery among persons with migraine - M. Reinhard; E. Wehrle-Wieland; M. Roth; W. D. Niesen; J. Timmer; C. Weiller; A. Hetzel (Experimental Brain Research, 2007)

The predatory behavior of wintering Accipiter hawks: temporal patterns in activity of predators and prey - Timothy C. Roth; Steven L. Lima (Oecologia, 2007)

Reciprocal Relationships Between Exotic Rusty Crayfish, Macrophytes, and Lepomis Species in Northern Wisconsin Lakes - Brian M. Roth; Jakob C. Tetzlaff; Mara L. Alexander; James F. Kitchell (Ecosystems, 2007)

Determinants of predation risk in small wintering birds: the hawk’s perspective - Timothy C. Roth; Steven L. Lima; William E. Vetter (Behavioral Ecology and Sociobiology, 2006)

Effect of In Vivo Administration of Ethylmalonic Acid on Energy Metabolism in Rat Tissues - Gustavo da C. Ferreira; Karina Roth André; Patrícia Fernanda Schuck; Carolina M. Viegas; Anelise Tonin; Daniella de Moura Coelho; Angela T. S. Wyse; Clóvis M. D. Wannmacher; Carmen R. Vargas; Moacir Wajner (Metabolic Brain Disease, 2006)

Computer Technology Helps Family Forest Owners in Pennsylvania and Washington - Paul A. Roth; James C. Finley; Kevin W. Zobrist; David M. Baumgartner (Journal of Forestry, 2006)
The use of computer technology in managing family forestlands is increasing. Growth, treatment, and visualization models can facilitate better understanding and communication of sustainable forest management concepts. Learning to use these tools can be challenging, and the technology has not been widely adopted at the landowner level. The Landscape Management System and associated Inventory Wizard have made these technologies easier to use and more accessible to landowners. Programs in Pennsylvania and Washington are promoting the use of this system by family forest owners.

Seasonal cycle in vitamin A1/A2-based visual pigment composition during the life history of coho salmon (Oncorhynchus kisutch) - S. E. Temple; E. M. Plate; S. Ramsden; T. J. Haimberger; W.-M. Roth; C. W. Hawryshyn (Journal of Comparative Physiology A, 2006)

BUBBLE – an Urban Boundary Layer Meteorology Project - M. W. Rotach; R. Vogt; C. Bernhofer; E. Batchvarova; A. Christen; A. Clappier; B. Feddersen; S.-E. Gryning; G. Martucci; H. Mayer; V. Mitev; T. R. Oke; et al. (Theoretical and Applied Climatology, 2005)

Polymorphic variation of CYP1A1 is associated with the risk of gastric cardia cancer: a prospective case?cohort study of cytochrome P-450 1A1 and GST enzymes - Mark J. Roth; Christian C. Abnet; Laura Lee Johnson; Steven D. Mark; Zhi Wei Dong; Philip R. Taylor; Sanford M. Dawsey; You-Lin Qiao (Cancer Causes & Control, 2004)

Spatiotemporal expression patterns of sialoglycoconjugates during nephron morphogenesis and their regional and cell type-specific distribution in adult rat kidney - Christian Zuber; Harry C. Winter; Irwin J. Goldstein; Jrgen Roth; James C. Paulson; Valeriu Toma (Histochemistry and Cell Biology, 2003)

Limnological effects of anthropogenic desiccation of a large, saline lake, Walker Lake, Nevada - Marc W. Beutel; Alex J. Horne; James C. Roth; Nicola J. Barratt (Hydrobiologia, 2001)

The Occurrence and Distribution of Selected Trace Elements in the Upper Rio Grande and Tributaries in Colorado and Northern New Mexico - H. E. Taylor; R. C. Antweiler; D. A. Roth; T. I. Brinton; D. B. Peart; D. F. Healy (Archives of Environmental Contamination and Toxicology, 2001)

Application of a lectin from the mushroom Polysporus squamosus for the histochemical detection of the NeuAcα2,6Galβ1,4Glc/GlcNAc sequence of N-linked oligosaccharides: a comparison with the Sambucus nigra lectin - Valeriu Toma; Christian Zuber; Harry C. Winter; Irwin J. Goldstein; Jürgen Roth (Histochemistry and Cell Biology, 2001)

Optomotor and neuropsychological performance in old age - C. Klein; B. Fischer; K. Hartnegg; W. H. Heiss; M. Roth (Experimental Brain Research, 2000)

Geostrophic Wind, Gradient Wind, Thermal Wind And The Vertical Wind Profile – A Sample Analysis Within A Planetary Boundary Layer Over Arctic Sea-Ice - R. Roth; M. Hofmann; C. Wode (Boundary-Layer Meteorology, 1999)

Anthropogenic change in subtropical dry forest during a century of settlement in Jaiquí Picado, Santiago Province, Dominican Republic - Linda C. Roth (Journal of Biogeography, 1999)
Summary Aim The dry forests of the tropics have received little scholarly attention relative to their significance and their rate of disappearance. This study aimed to characterize the structure and composition of two intermingled Antillean subtropical dry forest types and shed light upon their origins, development, and possible future conditions. Location Jaiquí Picado, Santiago Province, Dominican Republic (19° 26′ N, 70° 54′ W). Methods Biophysical data from quadrat sampling of vegetation, soils, and site characteristics were subjected to cluster analysis, means comparisons, discriminant analysis, and linear regression. Extensive interviews with local land users provided information on early forests as well as present and historical land use practices. Results Spatial patterning of the area's two main forest types relates closely to past land use but not to any observed differences in the physical characteristics of their sites. ‘Old‐growth’ stands found on land never placed in cultivation resemble the forests encountered by late‐nineteenth‐century settlers of the area in their wealth of woody plant taxa and relative abundance of endemic and other native species. In the ‘scrub’ stands growing on land abandoned from grazing, fully 70% of stems belong to one native ( Acacia macracantha Willd.) and two exotic ( Haematoxylon campechianum L. and Prosopis juliflora (Sw.) DC.) woody legumes that contribute to the markedly greater representation of deciduous and thorn‐bearing individuals in this type. The two forest types do not differ significantly in average bole dimensions, but the canopies of scrub stands are concentrated in a narrower layer, their understories are more open, and they contain more multiple stems of apparent sprout origin. A chronosequence of scrub stands covering a range in age of three decades indicates a moderate increment in species diversity over time and gradual disappearance of some of the more abundant invasive shrubs; but such stands continue to be dominated throughout this period by the same three scrub trees, while most species characteristic of old‐growth forests, including many of the least abundant, fail to appear among the regeneration in their understories. Main conclusions Antillean forests classified as thorn scrub may include a form of ‘disclimax’ created through past land use activities in areas once bearing more diverse tropical dry forest. Whether they will ever develop into stands similar to the previous forests is uncertain, given the present state of fragmentation and other processes taking place within these ecosystems.

Efferent synaptic connections of dopaminergic neurons grafted into the caudate nucleus of experimentally induced parkinsonian monkeys are different from those of control animals - C. Leranth; John R. Sladek Jr.; Robert H. Roth; D. Eugene Redmond Jr. (Experimental Brain Research, 1998)

Preliminary Studies on the Population Genetics of the Central Stoneroller (Campostoma anomalum) from the Great Miami River Basin, Ohio - R. N. Silbiger; S. A. Christ; A. C. Leonard; M. Garg; D. L. Lattier; S. Dawes; P. Dimsoski; F. McCormick; T. Wessendarp; D. A. Gordon; A.C. Roth; M. K. Smith; et al. (Environmental Monitoring and Assessment, 1998)

Enriched atmospheric CO 2 and defoliation: effects on tree chemistry and insect performance - Sherry Roth; Richard L. Lindroth; John. C. Volin; Eric. L. Kruger (Global Change Biology, 1998)
We examined the effects of CO 2 and defoliation on tree chemistry and performance of the forest tent caterpillar , Malacosoma disstria . Quaking aspen ( Populus tremuloides ) and sugar maple ( Acer saccharum ) trees were grown in open‐top chambers under ambient or elevated concentrations of CO 2 . During the second year of growth, half of the trees were exposed to free‐feeding forest tent caterpillars, while the remaining trees served as nondefoliated controls. Foliage was collected weekly for phytochemical analysis. Insect performance was evaluated on foliage from each of the treatments. At the sampling date coincident with insect bioassays, levels of foliar nitrogen and starch were lower and higher, respectively, in high CO 2 foliage, and this trend persisted throughout the study. CO 2 ‐mediated increases in secondary compounds were observed for condensed tannins in aspen and gallotannins in maple. Defoliation reduced levels of water and nitrogen in aspen but had no effect on primary metabolites in maple. Similarly, defoliation induced accumulations of secondary compounds in aspen but not in maple. Larvae fed foliage from the enriched CO 2 or defoliated treatments exhibited reduced growth and food processing efficiencies, relative to larvae on ambient CO 2 or nondefoliated diets, but the patterns were host species‐specific. Overall, CO 2 and defoliation appeared to exert independent effects on foliar chemistry and forest tent caterpillar performance.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Behavioral ecology ofMyiopharus doryphorae (riley) andM. aberrans (townsend), tachinid parasitoids of the colorado potato beetle - E. R. López; L. C. Roth; D. N. Ferro; D. Hosmer; A. Mafra-Neto (Journal of Insect Behavior, 1997)

Carbon dioxide exchange across the walls of arterioles: Implication for the location of the medullary chemoreceptors - J. Milton Adams; Christine Banka; Walter E. Wojcicki; Allan C. Roth (Annals of Biomedical Engineering, 1988)